Later Platonists and their Heirs among Christians, Jews, and Muslims - Anagnostou-Laoutides, Eva,; Parry, Ken, (Biblical Studies, Ancient Near East and Early Christianity E-Books Online, Collection 2023., 2023)
Later Platonists and their Heirs among Christians, Jews and Muslims offers a thought-provoking exploration of the reception of Platonism among communities of faith from early Christianity to the sixteenth century, from the Byzantine East to the Latin West. Rare emphasis is placed on the importance of Platonic thought and its diffusion in late antique and medieval Syria, Armenia, and Georgia but also among Arab and Jewish intellectuals from the seventh century onwards. As such, the volume makes a statement against the separation of Neoplatonic philosophy from Christianity and the other Abrahamic faiths, since all four traditions promoted a life of virtue and goodness despite operating under different divine auspices. The volume seeks to establish paths of transmission and modes of adaptation across times and places.